The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0102-67202012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Estudos endoscópico e histológico prospectivos e sequenciais da bolsa gástrica em 130 pacientes obesos mórbidos submetidos à bypass gástrico em Y-de-Roux

Abstract: -Background -Roux-en-Y gastric bypass is the most common performed bariatric surgery. A small gastric pouch is created, leaving a narrow gastrojejunal anastomosis, with a long jejunal limb. Very little is known regarding the behavior of this pouch years after surgery. Aim -To determine through prospective sequential endoscopic studies the size of the gastric pouch, the diameter of the anastomosis, and the behavior of H. pylori infection after surgery. Methods -In 130 patients subjected to resectional gastric b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Other authors, analyzing the gastric pouch and the presence of HP, have found no association between the presence of HP and the gastric pouch or gastrojejunal anastomosis size. These authors concluded that the behavior of HP is inconsistent and difficult to interpret 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors, analyzing the gastric pouch and the presence of HP, have found no association between the presence of HP and the gastric pouch or gastrojejunal anastomosis size. These authors concluded that the behavior of HP is inconsistent and difficult to interpret 9 .…”
Section: Discussionmentioning
confidence: 99%
“…After pouch creation, the mucosa remains normal where parietal cells are plentiful and the pouch does not dilate. 14,15 Because the pouch contains a small amount of gastric corpus, the total amount of acid secreted is small. 16,17 However, because parietal cells secrete approximately 150 mmol/L HCl (pH, ~0.8), the intrapouch pH is generally low.…”
Section: The Gastric Pouch and Acid Secretionmentioning
confidence: 99%